An examination of sales performance indicators for international live music events in Turkey - Açar, Aziz Fırat. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Music industry has been disrupted tremendously by the digital economy. As a result, live music events, instead of record sales, has become a major driver of the industry with growing number of performers, diverse audiences and outlets of live performances. So, understanding live music event success should be an important research subject. However, there is a literature gap in explaining this phenomenon. In the literature, live events are considered as an experience good and experience can take various forms as part of audience research. On the other hand, this study specifically aims to explore the live music events and their sales performance indicators. A sample of 131 live music events, performed at Zorlu Performing Arts Center between the years 2016 and 2018 have been employed for the study. Findings reveal that the brand related variables, distribution related variables and objective features have significant effects on the sales performances of those events.
Keywords: Music trade.; Music -- Economic aspects.